1994
DOI: 10.1093/geronj/49.3.s137
|View full text |Cite
|
Sign up to set email alerts
|

Race and Gender Differences in Religiosity Among Older Adults: Findings From Four National Surveys

Abstract: Using data from four national surveys, this article presents findings on racial and gender differences in religiosity among older adults. Surveys include the second Quality of American Life study, the Myth and Reality of Aging study, wave one of Americans' Changing Lives, and the 1987 sample of the General Social Survey. These four data sources collectively include a broad range of items which tap the constructs of organizational, nonorganizational, and subjective religiosity. In all four studies, and for most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
270
3
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(316 citation statements)
references
References 10 publications
40
270
3
3
Order By: Relevance
“…Finally, the average score obtained by those with a religious affiliation was almost four times that of those without an affiliation (47.5 vs. 13.3). Scores were also highest in minority groups (Black and Hispanic), which has often been reported using other measures of religiosity [43] [44].…”
Section: Discussionsupporting
confidence: 54%
“…Finally, the average score obtained by those with a religious affiliation was almost four times that of those without an affiliation (47.5 vs. 13.3). Scores were also highest in minority groups (Black and Hispanic), which has often been reported using other measures of religiosity [43] [44].…”
Section: Discussionsupporting
confidence: 54%
“…The reasons why the focus of spirituality research has been more on African Americans are not clear. However, research suggests that people from an African background view religion or spirituality to be more important in their lives and that they are more likely to pray privately, practise religious rituals, attend religious services, and believe that the Bible is the word of God (Jacobson et al, 1990;Levin et al, 1994). Ultimately, it is questionable whether these studies sufficiently reflect the range of individuals who are affected by ESRD, in terms of different cultures and different backgrounds, and whether it was these characteristics that influenced the findings of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…10 Indeed, African-Americans have been found to be more religious than whites, but the impact of religiosity on race differences in depression is rarely empirically explored. [10][11][12][13][14] Influence of Religious Service Attendance Studies have shown that religiosity is associated with positive health outcomes such as less smoking, drinking, and lower blood pressure. [15][16][17] Similar findings have reported an association between religious service attendance and lower odds of depression in African-American and white populations.…”
mentioning
confidence: 99%